Modelling of enteric bacteria concentrations in a river in Akure Nigeria. Issue 11 (27th October 2022) - Olalemi, Adewale Oluwasogo; Ogundare, Oluwatosin Temitope
Abstract: Models that can predict the level of faecal pollution in rivers are of great significance in low-and middle-income countries where residents rely on them for anthropogenic activities. Water samples from River Ala were collected from seven representative monitoring points and the load of enteric bacteria were determined. The physicochemical characteristics were determined, linear regression models and risk maps for the representative monitoring points on River Ala were developed. The concentration of Escherichia coli in the water samples from River Ala ranged from 4.87 to 5.41 log10 CFU 100 ml −1 and faecal coliforms 5.23 to 5.42 log10 CFU 100 ml −1 . Temperature ranged from 26.75 to 27.50 °C and turbidity 25.10 to 36.86 NTU. E. coli had positive relationships with turbidity (r = 0.62) and rainfall (r = 0.73). Faecal coliforms had positive relationships with turbidity (r = 0.76) and rainfall (r = 0.72). Regression models produced for rainfall as a function of E. coli had R² value of 0.667; and rainfall as a function of faecal coliforms had R² value of 0.683. The developed models demonstrated high predictive values and application to other monitoring points on the course of River Ala and can be adopted in water safety plans and water management practices. HIGHLIGHTS: High levels of faecal contamination at the different representative monitoring points. Physicochemical parameters and rainfall at 12 h before sampling influenced the load of enteric bacteria. Risk maps showed areas highly prone to faecal pollution. Human activities affected all regions in the representative monitoring points. Graphical Abstract